PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA CAFE BATAVIA JAKARTA - Chaerunisa Amelia (Panorama Nusantara, 2017)
This study aims to determine the effect of service quality and product quality on customer satisfaction at Cafe Batavia Jakarta. The type of data in this study is primary or data derived from respondents to determine dimensions of service quality, product quality, and customer satisfaction. Data collection collected by questionnaire instrument. The population in this study were all consumers of Cafe Batavia Jakarta with a sample of 100 respondents and randomly distributed by Accidental Sampling. The method of analysis using descriptive and quantitative methods, by multiple regression analysis. From the results of research on partial variables, the value of t is greater than t table, then Ha shows and states there is a positive and significant influence between service quality and product quality to customer satisfaction. While the percentage of influence on the quality of service and product quality given to consumers Cafe Batavia Jakarta amounted to 44,5%, while the rest influenced by other variables such as price factors, location factors and others.